German colonialism : race, the Holocaust, and postwar Germany - Langbehn, Volker Max 1959- HerausgeberIn; Salama, Mohammad HerausgeberIn (Columbia University Press, 2011)
Introduction: Reconfiguring German colonialism / Volker Langbehn and Mohammad Salama -- pt. 1. Colonial (dis)continuities : framing the issue -- Borrowed light : Nietzsche and the colonies / Timothy Brennan -- German colonialism : some reflections on reassessments, specificities, and constellations / Birthe Kundrus -- pt. 2. Lebensraum and genocide -- Against "human diversity as such" : Lebensraum and genocide in the Third Reich / Shelley Baranowski -- Hannah Arendt, imperialisms, and the Holocaust / A. Dirk Moses -- Caesura, continuity, and myth : the stakes of tethering the Holocaust to German colonial theory / Kitty Millet -- pt. 3. Looking East : Poland, the Ottoman Empire, and politicized Jihadism -- Germany's adventures in the Orient : a history of ambivalent semicolonial entanglements / Malte Fuhrmann -- Arguing the case for a colonial Poland / Kristin Kopp -- Colonialism, and no end : the other continuity theses / Russell A. Berman -- pt. 4. Of missionaries, economics, and intranational self-perception -- The purpose of German colonialism, or, The long shadow of Bismarck's colonial policy / Hartmut Pogge von Strandmann -- Christian missionary societies in the German colonies, 1884/85-1914/15 / Ulrich van der Heyden -- German colonialism and the British neighbor in Africa before 1914 : self-definitions, lines of demarcation, and cooperation / Ulrike Lindner -- pt. 5. Postcolonial German politics -- "Kalashnikovs, not Coca-Cola, bring self-determination to Angola" : the two Germanys, Lusophone Africa, and the rhetoric of colonial difference / Lu(c)Ưs Madureira -- Germany, Palestine, Israel, and the (post)colonial imagination / Martin Braach-Maksvytis